2014
DOI: 10.1179/2049396714y.0000000089
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms, lung functions, and exhaled nitric oxide (FENO) in two types of fish processing workers: Russian trawler fishermen and Norwegian salmon industry workers

Abstract: Objective: Respiratory outcomes and work-related factors were studied in two seafood worker populations representing different occupational environments. Methods: Levels of fractional exhaled nitric oxide (FE NO ), spirometric values, prevalence of respiratory symptoms, and self-evaluated exposures were compared between 139 Norwegian salmon workers and 127 Russian trawler workers. Results: Increased odds ratios (ORs) of shortness of breath with wheezing and prolonged cough as general respiratory symptoms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…92,93 Since the occupational and environmental component of the 2006 ACCP Consensus Statement on chronic cough 3 appeared in print, several additional publications have reported chronic cough to be associated with work exposures. Examples showing the range and frequency include mild steel welding with metal and gas exposure such as manganese and ozone (in 24% of workers), 94 seafish processing, 95 compost workers and garbage collectors. 96,97 Among Egyptian textile workers, chronic cough was reported in 33% compared with 6% of control subjects, 98 and among brick kiln workers in Pakistan, 22% had a chronic cough.…”
Section: Clinical Approach To Diagnosis and Management Of Laryngeal Dmentioning
confidence: 99%
“…92,93 Since the occupational and environmental component of the 2006 ACCP Consensus Statement on chronic cough 3 appeared in print, several additional publications have reported chronic cough to be associated with work exposures. Examples showing the range and frequency include mild steel welding with metal and gas exposure such as manganese and ozone (in 24% of workers), 94 seafish processing, 95 compost workers and garbage collectors. 96,97 Among Egyptian textile workers, chronic cough was reported in 33% compared with 6% of control subjects, 98 and among brick kiln workers in Pakistan, 22% had a chronic cough.…”
Section: Clinical Approach To Diagnosis and Management Of Laryngeal Dmentioning
confidence: 99%
“…The association between occupational exposure to cold temperatures and lung function has been little studied. Shiryaeva et al ( 2015 ) found FEV 1 , FVC and FEV 1 /FVC within the limits of normality among trawler fishermen and workers in salmon processing plant who were regularly exposed to moderately cold temperatures (Shiryaeva et al 2015 ). Although the findings of this study, like ours, suggest no association between cold temperatures and lung function, their cross-sectional design does not allow to draw conclusions about the development of lung function parameters over time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on occupational cold exposure have focused on the association with respiratory symptoms, but not on lung function data (Piedrahita et al 2008 ; Ghani 2020 ; Stjernbrandt et al 2021 ; Stjernbrandt et al 2022 ). Other studies, which monitored lung function parameters and occupational cold exposure, were either cross-sectional (Shiryaeva et al 2015 ) or had a short follow-up (Jammes et al 2002 ). However, in the present study, the semiannual surveys over 10 years allowed a substantial number of measurement points ( n = 398) to be included in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have found a prevalence of 1.8% and 8.2%, respectively (22,36). The prevalence of fish allergy has been shown to vary between 2.6% and 6.3% (36,37). Other studies have found a sensitisation prevalence varying from 0% to 10.3% to different fish species (33,34,38,39).…”
Section: Fishmentioning
confidence: 98%